Keefektifan Teknik Cinematherapy untuk Mengurangi Kebiasaan Mengonsumsi Minuman Keras Mahasiswa Maumere Universitas PGRI Kanjuruhan Malang - Wulan Sari, Eva Kartika; Kowan, Lydia Marlina (JKI (Jurnal Konseling Indonesia), 2023)
Consuming too much alcohol will affect one's attitudes and actions. The factors that can trigger this habit can be in the form of an environment that has a habit of consuming liquor, joining friends, experimenting, and so on. Apart from that, consuming liquor is also usually used by some people as an escape from the problems that are being experienced, where the intoxicating effect of alcohol in liquor can provide a momentary sense of calm for those who consume it. This study aims to reduce the level of drinking habits in Maumere students with cienematherapy techniques with pre-experiments with a one-group pretest and post-test design. The research subjects were eight students who had high criteria for the habit of consuming liquor. Giving treatment using group counseling using Cinematherapy techniques for eight meetings. The data collection instrument in this study used a scale of student drinking habits which was given at the beginning and end of the treatment and observation of each meeting. The results of the study were in the form of observation sheets and the Wilcoxon Sign Rank Test showing changes in scores before and after treatment. So it can be concluded that the Cinematherapy technique is effective in reducing the habit of consuming liquor among Maumere students at Universitas PGRI Kanjuruhan Malang.